A histone deacetylase 7‐derived peptide promotes vascular regeneration via facilitating 14‐3‐3γ phosphorylation. (29th January 2020) - Yang, Junyao; Moraga, Ana; Xu, Jing; Zhao, Yue; Luo, Peiyi; Lao, Ka Hou; Margariti, Andriana; Zhao, Qiang; Ding, Wei; Wang, Gang; Zhang, Min; Zheng, Lei; et al.
Abstract: Histone deacetylase 7 (HDAC7) plays a pivotal role in the maintenance of the endothelium integrity. In this study, we demonstrated that the intron‐containing Hdac7 mRNA existed in the cytosol and that ribosomes bound to a short open reading frame (sORF) within the 5′‐terminal noncoding area of this Hdac7 mRNA in response to vascular endothelial growth factor (VEGF) stimulation in the isolated stem cell antigen‐1 positive (Sca1 + ) vascular progenitor cells (VPCs). A 7‐amino acid (7A) peptide has been demonstrated to be translated from the sORF in Sca1 + ‐VPCs in vitro and in vivo. The 7A peptide was shown to receive phosphate group from the activated mitogen‐activated protein kinase MEKK1 and transfer it to 14‐3‐3 gamma protein, forming an MEKK1‐7A‐14‐3‐3γ signal pathway downstream VEGF. The exogenous synthetic 7A peptide could increase Sca1 + ‐VPCs cell migration, re‐endothelialization in the femoral artery injury, and angiogenesis in hind limb ischemia. A Hd7‐7sFLAG transgenic mice line was generated as the loss‐of‐function model, in which the 7A peptide was replaced by a FLAG‐tagged scrabbled peptide. Loss of the endogenous 7A impaired Sca1 + ‐VPCs cell migration, re‐endothelialization of the injured femoral artery, and angiogenesis in ischemic tissues, which could be partially rescued by the addition of the exogenous 7A/7Ap peptide. This study provides evidence that sORFs can be alternatively translated and the derived peptides may play an important role in physiological processes including vascular remodeling. Abstract : VEGF induced the translation of a 7‐amino acid peptide (7A) from Hdac7 mRNA in mouse adventitial Sca1+ vascular progenitor cells, which formed a novel MEKK1‐7A‐14‐3‐3γ signal pathway downstream VEGF and contributed to vascular injury repair and neo‐angiogenesis in ischemic tissues. The deficiency of 7A peptide (7A‐null mice) retarded these processes, which could be rescued by exogenous 7A peptide.